2008
DOI: 10.1109/tpami.2007.1162
|View full text |Cite
|
Sign up to set email alerts
|

A Theory Of Frequency Domain Invariants: Spherical Harmonic Identities for BRDF/Lighting Transfer and Image Consistency

Abstract: Abstract-This paper develops a theory of frequency domain invariants in computer vision. We derive novel identities using spherical harmonics, which are the angular frequency domain analog to common spatial domain invariants such as reflectance ratios. These invariants are derived from the spherical harmonic convolution framework for reflection from a curved surface. Our identities apply in a number of canonical cases, including single and multiple images of objects under the same and different lighting condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In the literature, t is usually referred to as the half-cosine function. [32][33][34] It is important to remark that in general C(v) = C(−v). enough value of is used, this result can be generalized to any shape of the interface between phases in 2D as…”
Section: Iib Closed Formulation Of the Mil Tensormentioning
confidence: 99%
“…In the literature, t is usually referred to as the half-cosine function. [32][33][34] It is important to remark that in general C(v) = C(−v). enough value of is used, this result can be generalized to any shape of the interface between phases in 2D as…”
Section: Iib Closed Formulation Of the Mil Tensormentioning
confidence: 99%
“…In general, existing approaches in inverse lighting can be divided into two classes based upon their representation of lighting; basis representation and point representation. The basis representation has been widely adopted for recovering the low frequency lighting [2], [3], [4], [5]. Nimeroff et al [6] first used a linear combination of steerable basis functions to represent the lighting.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Ramamoorthi [7] has shown that the spherical harmonics basis function (SH) is an optimal basis function to represent the illumination of a convex Lambertian object. Most recently, Mahajan et al [5] employed the image restoration framework into inverse lighting. They used a wiener filter to robustly recover the low frequency lighting as well as to infer the high frequency lighting from the low frequency lighting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Content changing operations includes splicing and composition [17,18]. Contrast enhancement including statistical intrinsic fingerprints [7,16], Gamma correction [8], reverse engineering of double Jpeg compressed images [9], noise features [15].…”
mentioning
confidence: 99%